WORK MEDICINE AND BIOLOGICAL SOCIAL SECURITY: THE CONVERSION OF MEDICAL ACTION IN THE PRODUCTION OF EDUARDO CRUZ-COKE LASSABE (CHILE, 1938-1946). - Cárcamo Gebhardt, Nicolás Andrés (Revista de Historia Social y de las Mentalidades, 2021)
Eduardo Cruz-Coke Lassabe was one of the most influential figures in the Chilean medical-political scene of the 20th century. As a result of a positive consideration of he’s proposals of environmental intervention and he’s invariable political-economic orientation, has remained historiographically disconnected from currents related to scientific racism. This research stresses his medical-social work from the axes of race and class. Through the analysis of he’s project of “conversion of medical action” - surveillance of healthy assumptions and detection of latent morbidity of the working class - we can make a deeper reading regarding an integrated national health program wishing to curb claims for obtaining social rights.
Keywords: Eduardo Cruz-Coke Lassabe; Biological forecast; Work Medicine; Preventive medicine